Impacts of Ambient and Ablation Plasmas on Short- and Ultrashort-Pulse Laser Processing of Surfaces - Nadezhda M. Bulgakova; Alexei N. Panchenko; Vladimir P. Zhukov; Sergey I. Kudryashov; Antonio Pereira; Wladimir Marine; Tomas Mocek; Alexander V. Bulgakov (Micromachines, 2014)
In spite of the fact that more than five decades have passed since the invention of laser, some topics of laser-matter interaction still remain incompletely studied. One of such topics is plasma impact on the overall phenomenon of the interaction and its particular features, including influence of the laser-excited plasma re-radiation, back flux of energetic plasma species, and massive material redeposition, on the surface quality and processing efficiency. In this paper, we analyze different plasma aspects, which go beyond a simple consideration of the well-known effect of plasma shielding of laser radiation. The following effects are considered: ambient gas ionization above the target on material processing with formation of a “plasma pipe”; back heating of the target by both laser-driven ambient and ablation plasmas through conductive and radiative heat transfer; plasma chemical effects on surface processing including microstructure growth on liquid metals; complicated dynamics of the ablation plasma flow interacting with an ambient gas that can result in substantial redeposition of material around the ablation spot. Together with a review summarizing our main to-date achievements and outlining research directions, we present new results underlining importance of laser plasma dynamics and photoionization of the gas environment upon laser processing of materials.